EXPERIENTIAL MARKETING DAN PEMBENTUKAN LOYALITAS PELANGGAN - Ardisa, Chintata; Sutrisno, Sutrisno; Dewi, Titis Shinta (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2018)
When a marketer involves Experiential Marketing as a marketing approach to a product or service being sold (Andreani 2007: 7), will affect the increase brand awareness, brand equity, and customer loyalty. Use of experiential marketing to create brand loyal customers to the brand. The purpose of this research is to find out whether the experiential marketing (on sense, feel, think, act and relate) on Yamaha motorcycles affect customer loyalty, partially, simultaneously and know subdominant variable in influencing customer loyalty. Type of this research is quantitative research. The population is Yamaha motorcycle customers in the Yamaha Riders Federation Indonesia (YRFI) community of Malang. Simple random sampling technique be appointed 86 respondents, Test the validity and reliability to know the validity and reliability of the instrument. Data analysis using descriptive analysis technique, a test of classical assumption for multiple linear regression analysis. The results of the study found a positive and significant influence partially between (1) sense, (2) feel, (3) think, (4) act lifestyle (5) Relation to customer loyalty. Also found simultaneous influence between experiential marketing on customer loyalty. The dominant variable is the sub variable of feel.